Examination of moral decision-making attitudes of elite male basketball players and wrestlers according to variables of sport experience and mother, father education - Arslan, F.; Ziyagil, M.A.; Bastık, Canan (Horizon Research Publishing, 2018)
The purpose of this research was to examine the extent to which at sport moral decision making attitudes were applied by the athletes, and the factors that caused it. The research was based on the causal comparative research model. The research group consisted of a total of 475 athletes, of which 195 were basketball athletes randomly selected from seven geographical regions and 280 were wrestling athletes. Lee, Whitehead, & Ntoumanis [23] used data collection tools to measure the moral decision-making attitudes of athletes (Attitude Moral Decision Making in Youth Sport Questionnaire-AMDYSQ). Gürpınar [16] has adapted the "Moral Decision Making Attitudes Scale in Infrastructure Sports" to Turkish culture. Mann Whitney-U test was used in binary comparisons because data were not normally distributed. As a result of the research, Significant differences were found according to subscales of Moral decision-making attitudes in infrastructure sports, such as wrestling and basketball, according to the subscale of adopting competition affinity, cheating, and winning fairness. In individual and team sports, it can be said that the athletic experiences are firstly influenced by the educational level of the parents after the athletes gain moral behaviors. The results of the research were supported by the literature. © 2018 by authors, all rights reserved.
Keywords: Basketball education; Moral decision makings; Wrestling education